ACADEMIC MIGRATION FROM UKRAINE IN THE CONDITIONS OF MARTIAL LAW - Mozgova, Natalia; Shushkevich, Yevgenii (Proceedings of the National Aviation University Series Philosophy Cultural, 2023)
Introduction. The war has caused millions of Ukrainian people to flee their homes. Some refugees from Ukraine have crossed borders, and many more moved inside the country. According to UN estimates, this is the fastest migration crisis since the World War II, which provoked new challenges and intensified existing migration problems. The aim of the research is to study migration processes in Ukraine since the beginning of a full-scale war between Russia and Ukraine. The historical and comparative methods are the research methods. To have a whole understanding of migration processes in Ukraine, statistical, comparative, inductive, and deductive methods are used. Research results. More than ever before, scientists and educators are becoming subjects today for the formation of highquality human capital, which together with financial, natural, and physical resources are the foundation of the national wealth of Ukraine. But the scale of the academic migration processes in Ukraine is becoming threatening. According to the UN Refugee Agency, from February 2024, more than 17 million people from Ukraine have already emigrated. According to the results of a survey of the Office of the UN High Commissioner, 65% of the Ukrainians who left for the EU are not going to return to Ukraine. Discussion. Modern researchers define four waves of migration in the history of Ukraine. In general, the phenomenon of Ukrainian emigration and diaspora as parts of the world of Ukrainianism are a unique phenomenon of Ukrainian culture and history. The Ukrainian diaspora existed not only geographically, but also in cultural, political and even family isolation from the native land. Conclusions. If we compare today’s migrants from Ukraine who have appeared as a result of the unleashed full-scale war of Russia against Ukraine after February 24, 2022, then we will see that geographical, political, cultural, family connections are still preserved, and moreover to a certain extent becomes even more powerful. Firstly, it concerns academic, more precisely, educational migrants. After all, the process of online learning does not cease. Ukrainian school teachers work every day until lunch offline with children in the Motherland, and after lunch with children who are abroad. This is just for the higher education. Thanks to the Internet, neither a political nor a cultural connection is not lost. All classes with students are held in an online format, which enables the student youth to continue to get a higher education in Ukraine, wherever they are.